Immunohistochemical expression of androgen receptor in cutaneous basal cell carcinoma - Bartoš, Vladimír; Kullová, Milada (Journal of Pakistan Association of Dermatologists, 2019)
Background Androgen receptor (AR) is known to be expressed in a variety of skin tumors, including basal cell carcinoma (BCC). The aim of this study was to investigate an expression status of AR by immunohistochemistry in a set of cutaneous BCC. Material and Methods The study group consisted of 54 BCCs from 49 patients. Based on histomorphology, BCC subtypes were merged into non-aggressive (superficial and nodular subtypes) and aggressive (nodular-infiltrative and infiltrative subtypes) subgroups. Specific monoclonal antibody against AR was used for immunostaining. Results AR was expressed in 32 BCCs (59.3%). In superficial, nodular, nodular-infiltrative and infiltrative BCC subtypes, nuclear reactivity for AR was found in 70% (7/10), 73.1% (19/26), 35.7% (5/14) and 25% (1/4), respectively. A wide quantitative range of AR expression (1–90% of tumor tissue) was seen. There were twenty-seven cases (84.4%) with focal staining and five cases (15.6%) with diffuse staining. There was significantly lower rate of AR expression in BCCs exhibiting aggressive histomorphologic phenotype. No correlation between AR expression and anatomic location and gender was found. Conclusion Although cutaneous BCC is generally considered to be AR-positive neoplasm, in the present study, immunoreactivity for AR was detected only in about half of the cases. Most AR-positive tumors showed only focal staining. The pathologists should be aware of these findings, which may cause difficulties in distinguishing BCC from related AR-negative epithelial skin tumors.